A Case of Herpesvirus Infection on Freshwater-reared Coho Salmon Oncorthynchus kisutch in Japan - MIYAZAWA, Maki; IIDA, Kusuo; HORIUCHI, Mitsuyuki; NISHIMURA, Shin-ichiro; NAKATA, Minoru (Aquaculture Science, 1989)
In autumn 1987, a mortality of freshwater-reared coho salmon (Oncorhynchus kisutch; 6 months old and about 100 g body weight) had occured at Touhoku district in Japan. The water temperatures of culture ponds were 9-15°C and about 12°C at the peak of mortality. Oral administration of oxytetracycline resulted in a failure, so that the mortality reached 5.6% for three months. The moribund fishes showed external signs or internal signs such as eroded fins and white spot lesions in the liver. Characteristic histopathological changes, multiple foci of severe necrosis, were observed in liver sections. In the bacteriological approaches on seven fishes, Flexibacter columnaris infection and Renibacterium salmoninarum infection were observed on all fishes and on one fish, respectively. On the other hand, we succeeded in isolating viral agent from the diseased fishes using RTG-2 at 15°C. RTG-2 infected with the virus showed cytopathic effect characterized by syncytia without inclusion bodies. The maximum titer of the cell culture was approximately 106 TCID50/ml. The virus was acid, heat and ether labile. Replication of the virus was inhibited by IUdR. Hexagonal nucleocapsids, observed in nuclei and cytoplasm, measured of 85-95 nm in diameter and enveloped virions on cell surface about 160 nm. These features indicated that the virus was herpesvirus. The virus was neutralized by rabbit anti-OMV (Oncorhynchus Masou Virus) serum, but not by anti-Herpesvirus salmonis serum. The pathogenicity and oncogenicity of the virus were not examined, however, this is the first report of herpesvirus isolation from a natural epizootic of coho salmon.Further biochemical and serological examinations are needed to clarify the relationships between the virus and other salmonid herpesvirus, so we provisionally called the virus herpesvirus strain OK of coho salmon. These results suggested that the mortality of this case was caused by herpesvirus disease, columnaris disease and bacterial kidney disease.